“Directions For Improving and Developing the Capacity of Life Insurance” (Eurasian Scientific Herald, 2023)
In recent years, life insurance is popular in many countries day by day. Today, organizations are competing in complex business environments characterized by continuous changes in economic, social politico-legal and regulatory factors. The insurance sector along with other elements of marketing, as well as financial infrastructure, have been touched and influenced by the process of liberalization and globalization in Uzbekistan. In order to develop life insurance, many changes are being made. And this article will discuss how to find other ways to improve the system and enhance awareness among individuals. The customer is the king in the market. Life Insurance companies deal in intangible products. With the entry of private players, the competition is becoming intense. In order to satisfy the customer, every company is trying to implement a consumer behavior (CB) program